#### Question

Show that the general solution of the differential equation `dy/dx + (y^2 + y +1)/(x^2 + x + 1) = 0` is given by (*x* + *y *+ 1) = *A *(1 – *x *– *y* – 2*xy*), where *A *is parameter

#### Solution

Is there an error in this question or solution?

Solution Show that the General Solution of the Differential Equation `Dy/Dx + (Y^2 + Y +1)/(X^2 + X + 1) = 0` Is Given by (X + Y + 1) = A (1 – X – Y – 2xy), Where A Is Parameter Concept: General and Particular Solutions of a Differential Equation.